Assessment of the Impact of Metropolitan-Scale Urban Planning Scenarios on the Moist Thermal Environment under Global Warming: A Study of the Tokyo Metropolitan Area Using Regional Climate Modeling - Asuka Suzuki-Parker; Hiroyuki Kusaka; Yoshiki Yamagata (Advances in Meteorology)
Using a high-resolution regional climate model coupled with urban canopy model, the present study provides the first attempt in quantifying the impact of metropolitan-scale urban planning scenarios on moist thermal environment under global warming. Tokyo metropolitan area is selected as a test case. Three urban planning scenarios are considered: status quo, dispersed city, and compact city. Their impact on the moist thermal environment is assessed using wet-bulb globe temperature (WBGT). Future projections for the 2070s show a 2–4°C increase in daytime mean WBGT relative to the current climate. The urban scenario impacts are shown to be small, with a −0.4 to +0.4°C range. Relative changes in temperature and humidity as the result of a given urban scenario are shown to be critical in determining the sign of the WBGT changes; however, such changes are not necessarily determined by local changes in urban land surface parameters. These findings indicate that urban land surface changes may improve or worsen the local moist thermal environment and that metropolitan-scale urban planning is inefficient in mitigating heat-related health risks for mature cities like Tokyo.